A paradigm shift in giftedness research: integrating critical realism's ontology, epistemology, and methodology. - Kirca Demirbaga, Kubra (Journal of Critical Realism, 2024)
This paper discusses the integration of critical realist ontology, epistemology, and methodology into giftedness and gifted education research. Although there is no consensus about the complex nature of giftedness, a paradigmatic shift is underway, emphasizing the impact of contextual and social factors in shaping gifted performance. Despite this shift, the ontological, epistemological, and methodological stances are often overlooked, leading to an incomplete understanding of the complex interaction between individuals and their context and constraining the potential to offer realistic and functional interventions for gifted education. Critical realism enables us to explore complex interactions, generate hypotheses, identify causal mechanisms, advance theoretical frameworks, and construct functional interventions for policy practices with its ontological, epistemological, and methodological arguments. This work contributes to the field by showcasing how critical realism's core concepts and tenets can be applied to various aspects of giftedness and gifted education and suggesting multiple avenues for further research.